The use of case studies in improved teaching - Watson, Derrill (2020)
Derrill Watson POLICY SEMINAR Virtual Event - Food Policy Research and Capacity Development in Eurasia Co-Organized by the Eurasian Center for Food Security (ECFS), World Bank Group, and IFPRI DEC 2, 2020 - 07:30 AM TO 09:00 AM EST